The influence of helmet certification in motorcycle helmets protective performance - Nurul Qastalani, Radzuan; Mohd Hasnun Ariff, Hassan; Mohd Nadzeri, Omar; Khairil Anwar, Abu Kassim (Faculty Mechanical Engineering, UMP, 2024)
The convenience of online shopping has increased access to a vast array of helmet options and deals for motorcyclists. However, the e-commerce enables an influx of unverified and potentially hazardous helmets lacking the rigorous quality control into the market, hence, placing unaware bargain seekers at risk. The non-certified variants questions in terms of impact protection abilities because they visually look similar to certified helmets. This study compared certified full face and open face helmets against their non-certified counterparts by analysing injury predictor metrics. Using a test rig simulating 5.58 ± 0.29 m/s impacts, an anthropomorphic test device wearing both helmet types and certification statuses measured peak resultant linear and angular accelerations, head injury criterion alongside brain injury criteria scores. The data revealed comparable side and rear impact performance between non-certified and certified helmets. However, frontal impacts exposed deficiencies without certification. The non-certified full face helmets registered over twice the peak linear acceleration of certified while open face types still exceeded certified by 40% in frontal impacts. Additionally, non-certified full face helmets indicated up to 100% predicted concussion risks in side and frontal crashes based on the angular accelerations. The poorer frontal impact and elevated injury odds demonstrate certification's key safety advantages that certification should not be ignored while it still providing more protection than no helmet. However, individual needs to carefully select helmets due to performance differences of helmets. Riders should ultimately prioritize proven protection given the severe consequences of head trauma though non-certified may suffice for some low-risk environments.